MicroRNAs Regulating Renin–Angiotensin–Aldosterone System, Sympathetic Nervous System and Left Ventricular Hypertrophy in Systemic Arterial Hypertension - Alex Cleber Improta-Caria; Marcela Gordilho Aras; Luca Nascimento; Ricardo Augusto Leoni De Sousa; Roque Aras-Júnior; Bruno Solano de Freitas Souza (Biomolecules, 2021)
MicroRNAs are small non-coding RNAs that regulate gene and protein expression. MicroRNAs also regulate several cellular processes such as proliferation, differentiation, cell cycle, apoptosis, among others. In this context, they play important roles in the human body and in the pathogenesis of diseases such as cancer, diabetes, obesity and hypertension. In hypertension, microRNAs act on the renin–angiotensin–aldosterone system, sympathetic nervous system and left ventricular hypertrophy, however the signaling pathways that interact in these processes and are regulated by microRNAs inducing hypertension and the worsening of the disease still need to be elucidated. Thus, the aim of this review is to analyze the pattern of expression of microRNAs in these processes and the possible associated signaling pathways.